2021
DOI: 10.1016/j.heliyon.2021.e06821
|View full text |Cite
|
Sign up to set email alerts
|

Effects of storage temperature and packaging material on physico-chemical, microbial and sensory properties and shelf life of extruded composite baby food flour

Abstract: Background The storability and eventual quality of flour is influenced by the optimality of the storage conditions. The present study assessed the effect of storage temperature on extruded composite flour packed in different packages. Methods Oats, soybean, linseed and premix (sugar, salt, Moringa & fenugreek) were blended and extruded. The extruded flour was packed in paper, polyethene and woven polypropylene bags and stored at -18, 25, 35, 45 °C. Moisture content, fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 35 publications
(55 reference statements)
2
16
0
Order By: Relevance
“…In agreement with the latest results, Hematian Sourki et al ( 2021) revealed that the incorporation of lemon verbena essential oil into cookie formulation led to a considerable reduction in the increment rate of PV, p-AV, TOTOX, and acid values during 6-month storage, which was comparable to the treatment containing TBHQ as an antioxidant. a shelf period of 90 days (Forsido et al, 2021). The best color liking was related to the treatment stored in polyethylene at −18°C.…”
Section: Fatty Acid Ranciditymentioning
confidence: 94%
See 1 more Smart Citation
“…In agreement with the latest results, Hematian Sourki et al ( 2021) revealed that the incorporation of lemon verbena essential oil into cookie formulation led to a considerable reduction in the increment rate of PV, p-AV, TOTOX, and acid values during 6-month storage, which was comparable to the treatment containing TBHQ as an antioxidant. a shelf period of 90 days (Forsido et al, 2021). The best color liking was related to the treatment stored in polyethylene at −18°C.…”
Section: Fatty Acid Ranciditymentioning
confidence: 94%
“…The color alterations in different treatments were claimed to be due to the enzymatic browning of polyphenols (Forsido et al, 2021;Hu et al, 2017).…”
Section: Sensory Evaluationmentioning
confidence: 99%
“…The result obtained for moisture content is similar to water activity. This similarity could be due to vapor transmission through packaging materials (Forsido et al, 2021). Surface area of the packaging material is one of the factors affecting its water vapor permeability (Jaya & Das, 2005).…”
Section: Quality Of Stored Tomato Powdermentioning
confidence: 99%
“…In addition to that, woven PP bags are commonly used in developing countries. However, Forsido et al [ 99 ] discussed that the low moisture barrier led to chemical, physical, sensorial, and microbial changes of flour. Another successful approach for flour packaging that was used for decades, was bags made from cotton twill [ 13 ].…”
Section: Cereal and Confectionary Productsmentioning
confidence: 99%